Renewable energy as an airport revenue source - Barrett, Stephen B.; DeVita, Philip M.; Whiteman, Adam (Transportation Research Board, 2015)
"TRB's Airport Cooperative Research Program (ACRP) Report 141: Renewable Energy as an Airport Revenue Source explores challenges airports may anticipate when considering renewable energy as a revenue source. These considerations include the airport's geography and terrain, infrastructure, real estate, energy costs, public policy, regulatory and compliance requirements, tax credits, sponsor assurances, ownership, impacts to navigation and safety, security, staffing issues, and many others. The guidebook also includes detailed financial information on the cost and performance of projects that have been implemented by airports. The guidebook also includes an appendix available online that provides sample a request for proposals."-- Publisher's description.
At head of title: Airport Cooperative Research Program.
Appendix F is available online only.
Keywords: Renewable energy sources -- United States.; Energy industries -- United States.; Diversification in industry -- United States.; Airports -- United States -- Finance.; elektronické knihy; electronic books